Chemical mechanical polishing of germanium selectively grown on silicon - Tan, Bryan Yue Han (Nanyang Technological University, 2023)
This report reviews the importance of the Chemical and Mechanical Planarization (CMP) process for photonics applications and discusses the various factors that affect the quality of CMP, and how to achieve optimality of the slurry recipe. Germanium-on-silicon (GOS) waveguides are fabricated for the purpose of chemical sensing by identifying unique chemical fingerprints that are present due to the different molecular vibrational modes, in the mid-infrared region. A novel fabrication method for waveguide was experimented, by using selective epitaxial germanium on silicon, an alternative to blanket germanium on silicon. The selective epitaxial GOS has the potential for reduced propagation loss compared to the more conventional blanket germanium on silicon, achieving a propagation loss of 11.53dB/cm before CMP, and is expected to improve after CMP by reducing thickness non-uniformity and improving material surface quality.